Arquitetura e clima local: relações entre orientação solar, tipos de tempo e conforto térmico em edifícios habitacionais na cidade de Palmas-TO - Santos, Raphael de Sousa (Universidade Federal do Tocantins, 2021)
This study is an interdisciplinary scientific contribution on architecture and climate in the central region of Brazilian Cerrado, in the city of Palmas (TO). It was knowledge designed for the general population, professionals and academics with an interest in the development of building projects with better environmental comfort and less energy consumption. It addresses the influence of solar orientation and types of atmospheric weather on the radiation thermal gain, air temperature and thermal comfort inside the building. To obtain the data, two types of vertical housing in middle class residential condominiums were analyzed with different types of finishing pattern, number of floors, construction systems and location. The analyzes of the buildings were built based on data of indoor temperature and air humidity in the housing units, thermographic images of the facades, external temperature of the facades, volume of clouds in the sky and active air masses, simulations of sunlight, shading and gain in the thermal load of the facades of the buildings, solar radiation values and comfort inside the apartments, considering the heat index. The results obtained show that the west facade is not always the one with the worst thermal performance, and that apartments facing this orientation will not always have the worst thermal performance. It was possible to verify that the thermal gain in all the facades can vary according to the time of the year and the types of atmospheric weather. In summer, the west side does not show a constant behavior regarding thermal gain. In winter, the west stands out in the values reached in its temperature, together with the north facade, which receives solar radiation from sunrise to sunset. The material chosen for the wrapping of the building's facades can influence and even enhance the thermal gain, as is the case with color or the use of glass. The variations in the types of weather, more or less constant in autumn-winter, but very variable in spring-summer, demonstrate that this study does not exhaust the subject and point to the need for more research. As a result obtained in the interview with the city's architects, the economic factor and the mercantilist view of the real estate market are other variables that complicate this balance between building, thermal comfort and energy efficiency.